Unmasking administrative evil - Adams, Guy B.; Balfour, Danny L.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1998)
With 'Unmasking Administrative Evil', Guy Adams and Danny Balfour maintain that administrative evil, or destructiveness, is inherent in modern public administration.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Abuse of administrative power; Public administration -- Moral and ethical aspects; Electronic books